Heritability of dispersal in a rapidly spreading invasive spider. (January 2022) - Narimanov, Nijat; Bonte, Dries; Entling, Martin H.
Abstract : Dispersal is an inseparable feature of animal life and a major determinant of species distributions and range dynamics. However, the role of the genetic architecture of dispersal behaviour, and hence the potential for its evolution in range-expanding species, is poorly understood. Here, we aimed to determine the heritability of dispersal behaviour for an invasive dwarf spider, Mermessus trilobatus, which has undergone rapid range expansion in Europe in the last few decades. Our results showed that spider dispersal traits were repeatable for the parental generation and heritable through both dam and sire. Behaviours were similarly heritable for female and male offspring. Interestingly, offspring of highly dispersive dams and sires exhibited almost three times higher dispersal propensity than offspring of at least one low-dispersive parent. The substantially high dispersal behaviour of the offspring of strictly highly vagile dams and sires indicates its recessive inheritance in this species. Recessive inheritance could favour invasiveness by facilitating high dispersal in inbred founder populations at the invasion front and returning to nonexaggerated mobility soon after an increase in genetic diversity. Highlights: Dispersal propensity appeared to be recessively inherited in an invasive spider. Variation in dispersal was present despite a presumably small founder population. On average dam and sire contributed to 37% of individual variation in dispersal. Spiders' dispersal traits were consistent at the individual level. There is a potential to evolve for high dispersal at the invasion front.